Reduced Scale Experimental Modelling of Distributed Thermal Response Tests for the Estimation of the Ground Thermal Conductivity - Stefano Morchio (MDPI AG, 2021)
The knowledge of the ground thermal properties, and in particular the ground thermal conductivity is fundamental for the correct sizing of the Ground Coupled Heat Pump (GCHP) plant. The Thermal Response Test (TRT) is the most used experimental technique for estimating the ground thermal conductivity. This paper presents an experimental setup aimed to realise a suitable scale prototype of the real borehole heat exchanger (BHE) and the surrounding ground for reduced scale TRT experiments. The scaled ground volume is realised with a slate block. Numerical analyses were carried out to correctly determine suitable geometric and operational parameters for the present setup. The scaled heat exchanger, inserted into the block, is created with additive technology (3D printer) and equipped with a central electrical heater along its entire depth and with temperature sensors at different radial distances and depths. Present measurements highlight the possibility to reliably perform a TRT experiment and to estimate the slate/ground thermal conductivity with an agreement of about +12% with respect to measurements provided by a standard commercial conductivity meter on proper cylindrical samples of the same material and onto 10 different portions of the slate block.